Synthesis of Sr0.5Ba0.5Nb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Chemistry and Physics, 2005)
A gel was formed when an aqueous solution of BaCl2, SrCl2, NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I kHz is 1000. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-Tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides